Capacity of Cipager River Pollution Load in Cirebon Regency - Sultan Al Faridzi Anand; Yayok Suryo Purnomo (PT FORMOSA CENDEKIA GLOBAL, 2022)
According to the medium-term infrastructure investment plan (RPIJM) for the city of Cirebon, the raw water source for PDAM Cirebon City has been using the Cipaniis spring, whose discharge is decreasing day by day due to forest destruction on Mount Ciremai. The steps in the QUAL2Kw method are segment determination, sampling, laboratory testing, hydraulic data analysis, water quality, pollutant sources, scenario determination, running the QUAL2Kw program and calculation of pollution load capacity. River water quality parameters used in the QUAL2Kw application in this study were PH, temperature, DO, TSS, Ammonia, and Phosphate. Application of the QUAL2Kw method, in evaluating river pollution load carrying capacity period. The capacity of the Cipager River pollution load for 2022, for the highest capacity in 2022, the TSS parameter is in segment B (downstream research) of 372.53 kg/day, the DO parameter is in segment A – 1 of -29.86 kg/day day, the ammoniac parameter is in segment A – 1 of 3.43 kg/day, the phosphate parameter is in segment B (downstream of the research).